The corticotropin-releasing hormone network and the hypothalamic-pituitary- adrenal axis: Molecular and cellular mechanisms involved - Bonfiglio, Juan José (2011)
Corticotropin-releasing hormone (CRH) plays a key role in adjusting the basal and stress-activated hypothalamic-pituitary-adrenal axis (HPA). CRH is also widely distributed in extrahypothalamic circuits, where it acts as a neuroregulator to integrate the complex neuroendocrine, autonomic, and behavioral adaptive response to stress. Hyperactive and/or dysregulated CRH circuits are involved in neuroendocrinological disturbances and stress-related mood disorders such as anxiety and depression. This review describes the main physiological features of the CRH network and summarizes recent relevant information concerning the molecular mechanism of CRH action obtained from signal transduction studies using cells and wild-type and transgenic mice lines. Special focus is placed on the MAPK signaling pathways triggered by CRH through the CRH receptor 1 that plays an essential role in CRH action in pituitary corticotrophs and in specific brain structures. Recent findings underpin the concept of specific CRH-signaling pathways restricted to specific anatomical areas. Understanding CRH action at molecular levels will not only provide insight into the precise CRH mechanism of action, but will also be instrumental in identifying novel targets for pharmacological intervention in neuroendocrine tissues and specific brain areas involved in CRH-related disorders.